2017
DOI: 10.1016/j.joto.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of benign paroxysmal positional vertigo. A clinical review

Abstract: Benign paroxysmal positional vertigo (BPPV) is the most frequent episodic vestibular disorder. It is due to otolith rests that are free into the canals or attached to the cupulas. Well over 90% of patients can be successfully treated with manoeuvres that move the particles back to the utriculus. Among the great variety of procedures that have been described, the manoeuvres that are supported by evidenced-based studies or extensive series are commented in this review. Some topics regarding BPPV treatment, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 85 publications
1
9
0
Order By: Relevance
“…The diagnosis of BPPV is based on the different characteristics of the nystagmus elicited by the provoking manoeuvres ( Pérez-Vázquez and Franco-Gutiérrez, 2017 ). The comprehensive diagnosis of BPPV includes the specification of the affected semi-circular canal(s) and pathophysiology (canalolithiasis or cupulolithiasis) ( Von Brevern et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of BPPV is based on the different characteristics of the nystagmus elicited by the provoking manoeuvres ( Pérez-Vázquez and Franco-Gutiérrez, 2017 ). The comprehensive diagnosis of BPPV includes the specification of the affected semi-circular canal(s) and pathophysiology (canalolithiasis or cupulolithiasis) ( Von Brevern et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these positional tests, we found that the posterior canal was most commonly affected in patients with BPPV, the horizontal canal was less affected. This is in line with reported percentages in the literature of 80–90% for the posterior canal [ 30 ]. Frenzel goggles or video-oculoscopy were not available in this physiotherapy setting.…”
Section: Discussionsupporting
confidence: 93%
“…Epley's maneuver for treating posterior canal canalolithiasis (depicted in Figure 2 for a right-sided posterior canal-BPPV). 6 1. The patient is seated with the head turned 45 • to the affected side (right in this case).…”
Section: Exclusion Criteriamentioning
confidence: 99%